Some biolochemical and histopathological effects of different oral doses Ochratoxin A in male rats: Duraid A.Abbas1 , Mohammed K.Faraj1 and Abbas Razzaq Abed2 - Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was carried out to investigate the effects of Ochratoxin A (OTA) on the serum activity of AST, ALT and ALP, Glutathione (GSH) and liver, kidney and spleen histopathology .Twenty male rats divided equally into three treated groups dosed orally and daily with OTA doses (70, 140 and 210 μg/kg) for 20 day representing T1, T2 and T3 groups and the fourth group dosed daily with distilled water considered as control one. Biochemical result showed elevation in AST and ALT activity and decrease in ALP enzyme activity and GSH serum concentration of treated serum groups at 10 and 20 days of exposure to ochratoxin A these changes positively were proportional with increase OTA doses (dose dependent). Histopathological changes were noticed in liver, kidney and spleen of all treated groups including (necrosis, congestion, and infiltration of inflammatory cells and vacuolation of cytoplasm). The severities of these lesions are in dose dependent manner.